2021
DOI: 10.7554/elife.73668
|View full text |Cite
|
Sign up to set email alerts
|

Parallel processing by distinct classes of principal neurons in the olfactory cortex

Abstract: Understanding how distinct neuron types in a neural circuit process and propagate information is essential for understanding what the circuit does and how it does it. The olfactory (piriform, PCx) cortex contains two main types of principal neurons, semilunar (SL) and superficial pyramidal (PYR) cells. SLs and PYRs have distinct morphologies, local connectivity, biophysical properties, and downstream projection targets. Odor processing in PCx is thought to occur in two sequential stages. First, SLs receive and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
3
8
0
Order By: Relevance
“…Previous work has shown that only deeper layer neurons send projections to the OB, and the superficial semilunar cells lack feedback projections (Mazo et al, 2017, Diodato et al, 2016. A recent study (Nagappan and Franks, 2021) indicated that semilunar and principal cells have many common properties, with only subtle differences in response tuning -therefore, our results are likely to generalize to other principal cells in PC. A third caveat is that the axonal and bouton activity could be influenced by local bulbar circuitry and may not faithfully represent somatic activity in PC neurons.…”
Section: Limitations Of Our Studysupporting
confidence: 61%
“…Previous work has shown that only deeper layer neurons send projections to the OB, and the superficial semilunar cells lack feedback projections (Mazo et al, 2017, Diodato et al, 2016. A recent study (Nagappan and Franks, 2021) indicated that semilunar and principal cells have many common properties, with only subtle differences in response tuning -therefore, our results are likely to generalize to other principal cells in PC. A third caveat is that the axonal and bouton activity could be influenced by local bulbar circuitry and may not faithfully represent somatic activity in PC neurons.…”
Section: Limitations Of Our Studysupporting
confidence: 61%
“…The study of the role of the PCx in olfaction has recently been boosted by selective genetic techniques, allowing researchers to examine how the individual cellular components relate to olfaction ( Franks et al, 2011 ; Nagappan and Franks, 2021 ). The PCx, also known as the olfactory cortex, receives inputs from the OB and constructs a robust odor representation ( Bolding et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the yield decreases across days, perhaps due to a move from layer 2 towards 1 (2b to 2a), which would correspond to increasing proportion of semilunar cells. However, prior work has shown that semilunar cells are less selective for odors [ 56 ]. Thus, this hypothetical is not consistent with the current knowledge of how layers and selectivity interact.…”
Section: Discussionmentioning
confidence: 99%